Digital Empathy dan Moral Elevation: Implikasi untuk Pendidikan dan Pengembangan Karakter Siswa: Penelitian - Siska Putri Ayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of digital technology has given rise to new forms of empathy that emerge through online interactions, including digital empathy and moral elevation. In an educational context, these two concepts have significant potential in shaping students' attitudes, values, and prosocial behavior. This article aims to examine how digital empathy and moral elevation can be integrated into educational environments to support students' character development, through a literature review of relevant research. The synthesis of these two concepts suggests that students' exposure to empathetic narratives, inspiring moral actions, and digitally shared emotional experiences can trigger positive emotional resonance, increase social sensitivity, and strengthen the tendency for prosocial behavior. Furthermore, targeted and educational digital interactions can be a means to foster emotional validation, moral reflection, and the formation of supportive learning communities. These findings confirm that digital empathy and moral elevation are not only psychological phenomena developing in the digital space but can also be relevant pedagogical strategies to strengthen character education. The implications of this study provide a basis for educators to design digital media-based interventions that can foster empathy, moral integrity, and prosocial behavior in students.